2008
DOI: 10.1126/science.1163728
|View full text |Cite|
|
Sign up to set email alerts
|

Degradation of microRNAs by a Family of Exoribonucleases in Arabidopsis

Abstract: microRNAs (miRNAs) play crucial roles in numerous developmental and metabolic processes in plants and animals. The steady-state levels of miRNAs need to be properly controlled to ensure normal development. While the framework of miRNA biogenesis is established, factors involved in miRNA degradation remain unknown. Here, we show that a family of exoribonucleases encoded by the SMALL RNA DEGRADING NUCLEASE (SDN) genes degrades mature miRNAs in Arabidopsis. SDN1 acts specifically on single-stranded miRNAs in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
318
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(337 citation statements)
references
References 17 publications
7
318
1
6
Order By: Relevance
“…This methylation protects the sRNAs against exonucleolytic shortening and/or nontemplated nucleotide addition [53,54]. For example, Ramachandran and Chen [55] found reduced levels of miRNAs and siRNAs in hen1 Arabidopsis mutants, as well as miRNAs with nontemplated 3 terminal nucleotides and 3 end truncated miRNAs. In our data, we identified two siRNAs mapping the RNAi-5x insert, in very low abundance, but when relaxing the parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This methylation protects the sRNAs against exonucleolytic shortening and/or nontemplated nucleotide addition [53,54]. For example, Ramachandran and Chen [55] found reduced levels of miRNAs and siRNAs in hen1 Arabidopsis mutants, as well as miRNAs with nontemplated 3 terminal nucleotides and 3 end truncated miRNAs. In our data, we identified two siRNAs mapping the RNAi-5x insert, in very low abundance, but when relaxing the parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-species conservation of 39 modifications of miRNAs suggests that it is the sequence of the mature miRNA that is the primary determinant of these modifications, both in the wild type and the hen1 mutants. Loss-of-function mutations in the genes that catalyze truncation (possibly via SDN1 and 2) and uridylation (HESO1) have a clear impact on miRNA stability and accumulation (Ramachandran and Chen, 2008;Ren et al, 2012;Zhao et al, 2012b). Therefore, knowing that miRNAs vary substantially in numerous aspects of their biogenesis (e.g., expression, structure, processing, etc.…”
Section: Discussion the Process Of Plant Mirna 39 Truncation And Tailingmentioning
confidence: 99%
“…This ability to regain the original miRNA size after truncation and tailing implies a memory of the original length. These two examples also suggest that the truncation activity, possibly performed by the SDN family of exonucleases (Ramachandran and Chen, 2008), in cases like miR166 and miR163 could be upstream of the uridylation activity, as tailing may not occur until the miRNA is shortened to a certain length. Other patterns were also apparent, for example, miR156, which targets SPL genes to regulate developmental time (Poethig, 2009), and miR172, which represses the translation of AP2-domain transcription factors (A) To generate the data in (B), the canonical miRNA was removed and all remaining variants were renormalized to add to 100%, enriching the signal for 39 modified variants.…”
Section: Mirnas Are Differentially Truncated and Uridylated In Hen1 Mmentioning
confidence: 94%
See 1 more Smart Citation
“…To explore the mechanisms of this selective miRNA stabilization in detail, further studies will be necessary to identify the poly(U) polymerase for 39 uridylation and the 39-59 exonuclease that destroys miR-122. A recent study identified a family of the small RNA-degrading nuclease (SDN) that degrades mature miRNAs in Arabidopsis (Ramachandran and Chen 2008). A mammalian homolog of SDN might be a candidate gene involved in destabilization of miR-122.…”
Section: Resultsmentioning
confidence: 99%